Authorship representation in global emergency medicine: a bibliometric analysis from 2016 to 2020. Issue 6 (27th June 2022) - Garbern, Stephanie Chow; Hyuha, Gimbo; González Marqués, Catalina; Baig, Noor; Chan, Jennifer L; Dutta, Sanjukta; Gulamhussein, Masuma A; López Terán, Gloria Paulina; Manji, Hussein Karim; Mdundo, Winnie K; Moresky, Rachel T; Mussa, Raya Yusuph; et al.
Abstract : Introduction: High-income country (HIC) authors are disproportionately represented in authorship bylines compared with those affiliated with low and middle-income countries (LMICs) in global health research. An assessment of authorship representation in the global emergency medicine (GEM) literature is lacking but may inform equitable academic collaborations in this relatively new field. Methods: We conducted a bibliometric analysis of original research articles reporting studies conducted in LMICs from the annual GEM Literature Review from 2016 to 2020. Data extracted included study topic, journal, study country(s) and region, country income classification, author order, country(s) of authors' affiliations and funding sources. We compared the proportion of authors affiliated with each income bracket using Χ 2 analysis. We conducted logistic regression to identify factors associated with first or last authorship affiliated with the study country. Results: There were 14 113 authors in 1751 articles. Nearly half (45.5%) of the articles reported work conducted in lower middle-income countries (MICs), 23.6% in upper MICs, 22.5% in low-income countries (LICs). Authors affiliated with HICs were most represented (40.7%); 26.4% were affiliated with lower MICs, 17.4% with upper MICs, 10.3% with LICs and 5.1% with mixed affiliations. Among single-country studies, those without any local authors (8.7%) were most common among those conducted in LICs (14.4%). Only 31.0% of first authors and 21.3% of last authors were affiliated with LIC study countries. Studies in upper MICs (adjusted OR (aOR) 3.6, 95% CI 2.46 to 5.26) and those funded by the study country (aOR 2.94, 95% CI 2.05 to 4.20) had greater odds of having a local first author. Conclusions: There were significant disparities in authorship representation. Authors affiliated with HICs more commonly occupied the most prominent authorship positions. Recognising and addressing power imbalances in international, collaborative emergency medicine (EM) research is warranted. Innovative methods are needed to increase funding opportunities and other support for EM researchers in LMICs, particularly in LICs.